Produção de propagandas sociais radiofônicas e educação tutorial: uma proposta para a formação do profissional de comunicação - Gonzales, Lucilene dos Santos [UNESP]; Seródio, Daniele [UNESP] (My University, 2012)
Produce radio advertisements to convey social UNESP FM Radio. This is the purpose of “Agência PropagAção”, extension project of the Faculty of Arts, Architecture and Communication Unesp, Bauru, SP, composed of 15 students of Communication and Design, coordinated by the teacher responsible. This extension project, however, over the four years of operation, has evolved from a manufacturing space of advertisements for a creative environment where teaching and learning are associated with teaching, research and extension. In this group, converge knowledge from different areas of social communication, resulting in scientific research initiation, completion of course work and professional practice with the provision of community services. Organized as an advertising agency, teachers and students experience education tutorial, extracurricular, adding, as a collective, integrated and interdisciplinary knowledge for the training of professionals with technical expertise, scientific, technological and academic.

Produção de propaganda social radiofônica para a emissora educativa Radio Unesp FM. Este é o propósito da Agência Propagação, projeto de extensão da Faculdade de Arquitetura, Artes e Comunicação da Unesp, composto por 15 alunos, estudantes de Comunicação e Design, que em suas atividades, são coordenados pela Profa. Dra. Lucilene Gonzales. Pelo desenvolvimento e reconhecimento do projeto, atualmente, além da criação de propaganda social radiofônica, a agência evoluiu para um ambiente de educação, articulando ensino, pesquisa e extensão. Organizados como uma agência de propaganda, alunos e professora experimentam a educação tutorial em um ambiente multidisciplinar, que reúne técnicas profissionais, metodologia científica e compartilhamento de conteúdos estudados em sala de aula.
Keywords: Tutorial education; Extension; Research; Social advertisements; Agência Propagação; Educação tutorial; Ensino; Extensão; Pesquisa; Propaganda social